Understanding the wealth and work as a social values of modern society (Journal of Philosophy Culture and Political Science, 2018)
This article analyzes the phenomenon of wealth as a social value. Wealth in modern society is not just the existence of a certain amount of money or goods. Wealth has become valuable. It promoted through the media. And if before the pursuit of wealth was not encouraged, but now it has become one of the leading reference for people. Equally it changed value attitude to work. On the one hand, labor is the source of income, as well as an important regulator of mental equilibrium. On the other hand, the importances of the classic work has depreciated due to the rapid development of technology and strengthen the role of education. Under the classic work meant manual labor on actual production. But in today’s society it is important to increase the middle class, that is, educated people. The middle class is not engaged in manual labor. That is why the role of high professionalism in modern society. Therefore, due to the increasing role of the value of wealth and the transformation of labor in modern society is increasingly difficult to achieve social justice. Key words: social value, wealth, work, social equality, professionalism, risk.